Multimodal imaging for improved diagnosis and treatment of cancers. Issue 6 (9th September 2014) - Tempany, Clare M. C.; Jayender, Jagadeesan; Kapur, Tina; Bueno, Raphael; Golby, Alexandra; Agar, Nathalie; Jolesz, Ferenc A.
<x xml:space="preserve">Abstract</x> The authors review methods for image‐guided diagnosis and therapy that increase precision in the detection, characterization, and localization of many forms of cancer to achieve optimal target definition and complete resection or ablation. A new model of translational, clinical, image‐guided therapy research is presented, and the Advanced Multimodality Image‐Guided Operating (AMIGO) suite is described. AMIGO was conceived and designed to allow for the full integration of imaging in cancer diagnosis and treatment. Examples are drawn from over 500 procedures performed on brain, neck, spine, thorax (breast, lung), and pelvis (prostate and gynecologic) areas and are used to describe how they address some of the many challenges of treating brain, prostate, and lung tumors. Cancer 2015;121:817–827. © 2014 American Cancer Society.